FRAMEWORK FOR EXPLORING THE CONCEPT OF "LEADERSHIP" AND 8 COMMON LEADERSHIP STYLES (American Journal of Business Management, Economics and Banking, 2022)
Subject A person who plays a dominant role in the country, in the company, in the family, is gifted with the talent to rule the “minds” of people for subsequent success. The problem of leadership has always concerned the world as a whole and each person individually, being the key and relevant for many areas of life: business, politics, sports, etc., because leadership exists wherever there is collective activity and organization, this is what surrounds us every day. Therefore, a considerable number of studies and publications are devoted to this topic. This article explores the qualities of leadership, and their use in various situations, the nature of leadership, approaches to the study of leadership, the concept of leadership behavior.